Smart Tourism Technologies and Tourist Experience: A Systematic Literature Review - Pikrianto Pikrianto (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Smart Tourism Technologies (STTs) have become a key driver of digital transformation in the tourism industry, offering new opportunities to enhance tourist experiences and destination competitiveness. However, existing studies remain fragmented across different technological contexts and research perspectives. This study aims to systematically review the literature on the relationship between Smart Tourism Technologies and Tourist Experience. A Systematic Literature Review (SLR) was conducted following the PRISMA 2020 guidelines. Relevant articles were identified through international scholarly databases and analyzed using thematic analysis. The findings indicate that Artificial Intelligence (AI), Internet of Things (IoT), Big Data Analytics, Virtual Reality (VR), Augmented Reality (AR), and mobile applications are the most frequently studied technologies. These technologies positively influence tourist experience by improving information accessibility, personalization, interactivity, convenience, and satisfaction. Despite these benefits, challenges related to data privacy, digital inequality, and technological readiness remain significant. This review provides insights for researchers and practitioners while identifying future research opportunities in smart tourism.